In 'Trusts' We Trust: Socially Motivated Private Schools in Nepal - Sarmistha Pal; Bibhas Saha (Institute for the Study of Labor (IZA), 2014)
We study school choice and school efficiency in terms of secondary school completion test scores by utilizing a unique database from Nepal. There are two novel features of our analysis: firstly we allow for heterogeneity among private schools, by distinguishing socially motivated trust-run schools from profit-motivated company-run schools, and secondly, we include school's expenditure as a determinant of its efficiency per unit of cost. We find that when expenditure is not included, the trust-run school comes on top, slightly but distinctly, ahead of the profit-motivated school. But if expenditure is included, the trust-run school's position becomes sensitive to the level of expenditure, as it is the only school to exhibit sensitivity between expenditure and test score. In the urban area, the public school is always at the bottom, and between the two types of the private school the trust-run school ranks first (second) at high (low) levels of expenditure. However, in the rural area it is a three way race, with the trust school coming on top again at high expenditure, but falling to bottom at low levels of expenditure. This picture is fairly robust to considerations of subject fixed effects and to inclusion or exclusion of private aided schools or private tuition. We show both theoretically and empirically that socially motivated schools can be efficient and outperform profit-motivated schools.
Keywords: H44; I22; 330; private school heterogeneity; school expenditure per student; efficiency; private school premium; social objectives; private motive; rural-urban dichotomy; Nepal